A characteristic ganglioside antibody pattern in the CSF of patients with amyotrophic lateral sclerosis. Issue 4 (April 1993) - Stevens, A; Weller, M; Wiethölter, H
Abstract : Paired cerebrospinal fluid and serum samples of patients with amyotrophic lateral sclerosis (n = 35) revealed no consistent abnormalities of CSF cell count, CSF albumin, CSF IgG, CSF IgM, IgG or IgM index, or oligoclonal immunoglobulin band formation in the CSF. Determination of IgG and IgM CSF and serum antibodies to gangliosides GM1, GM2, GM3, AGM1, GD1a, GD1b, and GT1b showed a characteristic pattern which allowed the differentiation of amyotrophic lateral sclerosis from controls and from patients with other neurological disorders including multiple sclerosis. Specifically, patients with the disease had elevated CSF IgM antibodies to all gangliosides except AGM1. The lack of correlation between the CSF findings and corresponding serum antibodies suggests a chronic, compartmental, intrathecal immune response of low activity in amyotrophic lateral sclerosis. Whether this immune response is primary and of pathogenetic significance, or an epiphenomenon of neuronal degeneration, remains to be investigated.